2017
DOI: 10.1016/j.bbrc.2017.06.149
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα1 deficiency suppresses brown adipogenesis in favor of fibrogenesis during brown adipose tissue development

Abstract: Brown adipose tissue (BAT) dissipates energy for thermogenesis which reduces or prevents obesity and metabolic dysfunction. AMP-activated protein kinase (AMPK) is a master regulator of energy metabolism and its activity is inhibited in the developing BAT due to obesity. We previously found that AMPK is required for brown fat development and thermogenic function, but the non-brown adipogenic differentiation of progenitor cells due to AMPKα1 deficiency has not been defined. We found that, in vivo, the thermogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Our results indicate that WAT browning is associated with alteration of ECM composition. The inverse correlation between WAT browning and ECM is consistent with the suppression of brown adipogenesis in favour of fibrogenesis in mice 49 .
Figure 4 Transcriptomic analysis of the subcutaneous inguinal adipose tissue of postnatal Egr1 −/− versus Egr1 +/+ mice reveals downregulation of extracellular matrix genes.
…”
Section: Resultssupporting
confidence: 74%
“…Our results indicate that WAT browning is associated with alteration of ECM composition. The inverse correlation between WAT browning and ECM is consistent with the suppression of brown adipogenesis in favour of fibrogenesis in mice 49 .
Figure 4 Transcriptomic analysis of the subcutaneous inguinal adipose tissue of postnatal Egr1 −/− versus Egr1 +/+ mice reveals downregulation of extracellular matrix genes.
…”
Section: Resultssupporting
confidence: 74%
“…It is worth noting that many target genes were significantly enriched in the AMPK signaling pathway, which is a critical pathway for energy metabolism [62] and the browning of white adipocytes [63]. In addition, AMPK α1- and α2-subunit knockout reduced adipogenesis and thermogenic function in brown adipose tissue compared to wild-type mice [64,65]. In adipose tissue-specific knockout of AMPK β1- and β2-subunit mice, AMPK was essential for mitochondrial integrity and thermogenesis upon cold and β-adrenergic stimulation and promoted the browning of white adipose tissue [66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that reduction of pAMPK in WAT is widely observed in obese and diabetic rodents as well as in human subjects accompanied with insulin resistance [35]. In addition, deletion of AMPKα1 impaired the thermogenic program in BAT [36], which may result from the defective unwinding of the DNA of the promoter region of the PRDM16 [37]. These data suggest that activation of AMPK plays an important role in thermogenic function.…”
Section: Discussionmentioning
confidence: 78%